Moral permissibility of mandatory COVID-19 vaccinations amongst healthcare workers in South Africa - Badal-Faesen, Sharlaa (My University, 2022)
Background. The development of COVID-19 vaccines has been expedited resulting in many unanswered questions regarding their long-term safety and efficacy. Healthcare workers are regarded as high risk for getting infected as well as for transmitting the infection to their patients, colleagues, and families. Based on this high risk, policymakers and healthcare facilities may opt to mandate vaccinations of healthcare workers. Objective. To normatively analyse the moral permissibility of mandatory COVID-19 vaccinations of healthcare workers in South Africa. Methods. In this research report arguments to support the stance that vaccine mandates cannot be justified will be explored. Firstly, this report will give an overview of COVID-19 vaccines by addressing uncertainties regarding the longevity of the immune responses and long-term adverse effects. Vaccine hesitancy will also be addressed. Vaccination programmes have been successful as public health measures, however, this concept will be interrogated. Moral theories of Principalism, Kantianism, Utilitarianism and the Philosophy of Ubuntu will be explored to support the argument that vaccine mandates for HCWs is not morally permissible. Finally, the legality of vaccine mandates will be examined. Conclusion. The lack of long-term data regarding immune responses to COVID-19 vaccines together with the moral and legal arguments presented in this research report, support the argument that mandatory vaccinations of HCWs cannot be justified. However, the Philosophy of Ubuntu is proposed as a possible solution to the dilemma between individual rights and public health measures.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022